Community-wide mass drug administration for soil-transmitted helminths – risk of drug resistance and mitigation strategies - Pilotte, Nils; Manuel, Malathi; Walson, Judd L.; Ajjampur, Sitara S. R. (Frontiers in Tropical Diseases, 2022)
Mass drug administration programs for the control of soil-transmitted helminths (STH) in humans most commonly utilize a single class of drugs; the benzimidazoles. Most such programs focus on the treatment of pre-school and school aged children attending schools, although there is increasing interest in the potential utility of community-wide MDA to reduce infection intensity within communities and possibly to interrupt STH transmission. In animals, mass treatment with benzimidazoles leads to the rapid selection of parasites containing resistance-encoding single nucleotide polymorphisms (SNP) and the potential emergence of resistance in parasite species that infect humans is of major potential public health concern. As programs scale up delivery of anthelmintics and consider expanding treated populations, monitoring of drug efficacy and the potential emergence of anthelmintic resistance with sensitive diagnostic tools is critical to ensure the continued success of STH control programs. In particular, as programs consider the adoption of community-wide deworming, there is concern that such a strategy may increase the risk of drug resistance by limiting the number of untreated individuals which serve as a refugia of unexposed worm populations. We review the literature for evidence of drug resistance in human STH infections and explore risks and mitigation strategies for emergence of drug resistance in the context of community-wide deworming.